ANALISIS KONFLIK AGAMA DI SMK N 1 WONOSOBO BAGAIMANA PERBEDAAN AGAMA DI SEKOLAH MENIMBULKAN MASALAH DAN CARA MENGATASINYA - Fitri Hana Arlita; Elvia Nadiyah; Nurul Mubin (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research aims to analyze religious conflicts occurring at SMK Negeri 1 Wonosobo and how religious differences in the school environment can lead to issues and ways to address them. Differences in religious beliefs among students often become a source of tension, discrimination, and conflicts that negatively impact social relations within the school. This study uses a qualitative method with data collection through interviews, observations, and documentation. The results indicate that religious conflicts arise due to stereotypes, lack of interfaith understanding, and influences from the external environment outside the school. To address these conflicts, it is recommended to implement multicultural education programs, interfaith dialogue activities, and the establishment of school policies that support tolerance. The emergence of conflicts under the banner of religion indicates that Indonesia still lacks a comprehensive understanding of its multicultural internal conditions. Community differences should be the foundation for preserving identity through maintaining national integration, rather than as a trigger for intergroup conflict. Through multicultural Islamic education, this paper offers an alternative for resolving religious conflicts in Indonesia based on values embedded within Islamic teachings. Multicultural Islamic education can be used as a new approach to changing the way people think and perceive, as well as to enhance attitudes and behaviors within a diverse society. In this context, multicultural Islamic education instills a spirit of religious life based on the values of peace, tolerance, respect for diversity, and other attitudes that uphold human values and the spirit of Indonesian national unity. This research employs a qualitative approach to gain a deep understanding of religious conflicts at a single location (SMK N 1 Wonosobo) by observing interaction patterns, identifying involved actors, and analyzing conflicts that arise as well as the methods of addressing them. In-depth interviews with students, teachers, and school officials can provide rich data on their perceptions and experiences regarding religious differences in the school. If exploring the cultural and religious dynamics within the school environment is desired, the ethnographic method will help understand conflicts from the perspective of those directly involved. Researchers can observe daily interactions to identify sources of tension and the strategies employed by the school to address these issues